Left and agrarian conflict in a convulsed Argentina, 1970 - Lissandrello, Guido (2021)
In this article we examine the relationship between a political actor (the Communist Party) and a social actor (the Agrarian Leagues), in the convulsed 70’s in Argentina. While the first was one of the longest-running leftist parties in the country, the second corresponds to a complex social movement, which emerged at a juncture of economic crisis and important technological and productive transformations in agriculture. Studies on the political organizations of the period tended to focus on their links with urban social actors, thereby overshadowing the relationships that were woven with rural sectors, which did not escape the tone of protest of the time. In order to settle this deficit, we take this party that gave rural issues the most attention to understand how it was linked to the league movement and how it characterized it theoretically. Based on the study of its internal documents (congressional records) and public documents (theoretical magazines and newspapers), we reconstruct its defense of an Argentine peasantry, taking into account the contradictions in them.This approach would illuminate a current historiographic problem from another angle: the social nature of the Agricultural Leagues.